Bilingual Glossary of Clichés for Dubbing and Subtitling - Araújo, Vera Lúcia Santiago (The ESPecialist, 2012)
This article describes the entry of a bilingual glossary (English-Portuguese) made up of 250 clichés that express emotion in five dubbed and subtitled films. The glossary, taken from my Ph.D. research, has two formats. The first shows the clichés categorized according to one of the emotions analyzed in the thesis (joy, love, anxiety, anger, guilt, surprise, sympathy, sorrow, and irony). The second brings the complete entry by giving relevant information about the cliché: category of emotion; function; example of its use in English; translation into Portuguese; suggestions of translation; and related clichés which can be used in the same context.